An Examination of Hurricane Sandy: A Review of Savage Sand and Turf by Lisa A. Eargle and Ashraf Esmail (Ed.). Issue 1 (6th May 2016) - Valcik, Nicolas A.
Abstract : This article will review the edited book Savage Sand and Turf by Lisa A. Eargle and Ashraf Esmail. In this article, an examination is conducted on the different perspectives undertaken by each chapter author on how Hurricane Sandy impacted an entire region of the United States. The article will also review how the different academic disciplines have undertaken different research agendas with Hurricane Sandy in relation to disaster response and emergency management topics.